An investigation into perceptions of learner participation in the governance of secondary schools - Nongubo, Mphuthumi J (Rhodes University, Faculty of Education, Department of Education, 2005)
The question of learner participation or involvement in school governance has been a thorny issue in South Africa for decades. This study investigated secondary learners' participation in the governance of their schools through representation by the Representative Council of Learners (RCLs), formerly known as school representative councils (SRCs). The study attempted to find out how learners participation is perceived by both the RCLs and the School Management Teams (SMTs). The study was conducted in five secondary schools in the Eastern Cape townships of Grahamstown. The research participants were members of School Management Teams and Representative Councils of Learners from these schools. The study was oriented in an interpretive paradigm following a qualitative approach. Questionnaires and in-depth semi-structured interviews were used to explore the perceptions of the two groups involved. The Department of Education documents that sanction RCL participation were referred to throughout and especially when analysing the respondents' views. The main finding of the study is that learner involvement in school governance is still problematic, though it is presently provided for by policies that govern schools, including the South African Schools Act and the Guides for Representative Councils of Learners of 1999, in which their roles are outlined. The findings of the study reveal an indecisive and autocratic mindset among educators regarding the issue of learner involvement in governance and management. Furthermore, the Department of Education documents in place betray a narrow conception of RCL participation in school governance and still display an element of mistrust towards the learners concerning their roles in governance. As a result of these forces, the democratic potential of learner participation is undermined, and RCLs compromised as legitimate stakeholders.
Keywords: Education and state -- South Africa; School management and organization -- South Africa; Education, Secondary -- South Africa; Student government -- South Africa; Student participation in administration -- South Africa